Super-Agrobacterium ver. 4: Improving the Transformation Frequencies and Genetic Engineering Possibilities for Crop Plants - Nonaka, Satoko; Someya, Tatsuhiko; Kadota, Yasuhiro; Nakamura, Kouji; Ezura, Hiroshi (Frontiers in Plant Science, 2019)
Agrobacterium tumefaciens has been utilized for both transient and stable transformations of plants. These transformation methods have been used in fields such as breeding GM crops, protein production in plant cells, and the functional analysis of genes. However, some plants have significantly lower transient gene transfer and stable transformation rates, creating a technical barrier that needs to be resolved. In this study, Super-Agrobacterium was updated to ver. 4 by introducing both the ACC deaminase (acdS) and GABA transaminase (gabT) genes, whose resultant enzymes degrade ACC, the ethylene precursor, and GABA, respectively. A. tumefaciens strain GV2260, which is similar to other major strains (EHA105, GV3101, LBA4404, and MP90), was used in this study. The abilities of the Super-Agrobacterium ver. 4 were evaluated in Erianthus ravennae, Solanum lycopersicum ‘Micro-Tom’, Nicotiana benthamiana, and S. torvum. Super-Agrobacterium ver. 4 showed the highest T-DNA transfer (transient transformation) frequencies in E. ravennae and S. lycopersicum, but not in N. benthamiana and S. torvum. In tomato, Super-Agrobacterium ver. 4 increased the stable transformation rate by 3.6-fold compared to the original GV2260 strain. Super-Agrobacterium ver. 4 enables reduction of the amount of time and labor required for transformations by approximately 72 %, and is therefore a more effective and powerful tool for plant genetic engineering and functional analysis, than the previously developed strains. As our system has a plasmid containing the acdS and gabT genes, it could be used in combination with other major strains such as EHA105, GV3101, LBA4404, MP90, and AGL1. Super-Agrobacterium ver. 4, could thus possibly be a breakthrough application for improving basic plant science research methods.